2000
DOI: 10.1002/jccs.200000151
|View full text |Cite
|
Sign up to set email alerts
|

Taxane Diterpenoids from the Root Bark of Taiwanese Yew Taxus Mairei

Abstract: Nineteen compounds including taxumairol R (1), taxinine M (2), taxacin (3), paclitaxel (4), 10‐deacetyltaxol A (5), 10‐deacetyl‐7‐epi‐taxol (6), 7‐epi‐taxol (7), taxol C, 10‐deacetyltaxol C, 7β‐xylosyl‐10‐deacetyltaxol (8), taxamairin A (9), taxinine A, 14β‐hydroxytaxusin (10), 5α‐hydroxy‐7β,9α,10β, 13α‐tetraacetoxy‐4(20), 11‐taxadiene, 1‐dehydroxybaccatin‐VI, 1β‐dehydroxybaccatin‐IV, baccatin IV, baccatin VI and ponasterone A have been isolated and identified from the root bark of Taxus mairei. Among them, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…In the course of our systematic analysis of bioactive natural products from water extracts of Taxus chinensis, we have isolated 7-xylosyl-10-deacetylpaclitaxel (10,11). In the present investigation, we showed that 7-xylosyl-10-deacetylpaclitaxel reveals growth inhibitory activity against PC-3 cells, which is similar to that of paclitaxel at a fixed exposure time of 48 h.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In the course of our systematic analysis of bioactive natural products from water extracts of Taxus chinensis, we have isolated 7-xylosyl-10-deacetylpaclitaxel (10,11). In the present investigation, we showed that 7-xylosyl-10-deacetylpaclitaxel reveals growth inhibitory activity against PC-3 cells, which is similar to that of paclitaxel at a fixed exposure time of 48 h.…”
Section: Discussionsupporting
confidence: 55%
“…Water decoctions from the leaves of T. chinensis are used in traditional Chinese medicine to treat cancer, indicating that water soluble constituents of this tree may indeed possess anticancer activity. In an effort to search for natural products from T. chinensis with improved pharmacological features compared to paclitaxel, 7-xylosyl-10-deacetylpaclitaxel has been isolated and identified by our group (10,11). This is a naturally occurring xyloside, which has been shown to possess higher water solubility than paclitaxel (8,12).…”
Section: Introductionmentioning
confidence: 99%